2008
DOI: 10.1111/j.1745-4549.2008.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Local Canning Process and Storage on Pelagic Fish From Tunisia: Fatty Acid Profiles and Quality Indicators

Abstract: The present study was designed to assess the effect of local canning process and storage time (up to 6 months) on tuna and sardine canned in olive oil and tomato sauce, respectively. The canning process affected tuna (P < 0.05) but not sardine lipid levels. Canned tuna and sardine absorbed coating oil during sterilization, inducing a higher oleic (C18:1 w9) and linoleic (C18:2 w6) acid content. Independent of fish species, the eicosapentaenoic (C20:5 w3) and docosahexaenoic (C22:6 w3) acid concentrations range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
38
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 25 publications
9
38
3
Order By: Relevance
“…A low peroxide formation could be observed in all kinds of samples (<8.0; Table ) in agreement to previous research related to other canned species such as Atlantic bluefin tuna ( Thunnus thynnus ) and sardine ( Sardina pilchardus ) and Atlantic salmon ( Salmo salar ) . In the current study, peroxide assessment showed a marked decrease ( p < 0.05) as a result of the canning process (comparison between raw and canned control samples) (Table ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…A low peroxide formation could be observed in all kinds of samples (<8.0; Table ) in agreement to previous research related to other canned species such as Atlantic bluefin tuna ( Thunnus thynnus ) and sardine ( Sardina pilchardus ) and Atlantic salmon ( Salmo salar ) . In the current study, peroxide assessment showed a marked decrease ( p < 0.05) as a result of the canning process (comparison between raw and canned control samples) (Table ).…”
Section: Resultssupporting
confidence: 91%
“…Differently to most volatile amines, TMA is a non‐water‐soluble tertiary amine so that it is not likely to be leached into the present brine packing medium. According to the current work, a marked TMA content increase was observed after canning in tuna ( T. thynnus ) and sardine ( S. pilchardus ) muscle . Comparison among canned samples did not provide significant differences ( p > 0.05), so that a general trend about algae extract presence on the formation of this deteriorative molecule could not be implied.…”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…However, the PV obtained in all cases remained below the 8.3 score. A low peroxide content has also been detected in canned Atlantic bluefin tuna ( Thunnus thynnus ) and sardine ( Sardina pilchardus ) as well as in canned Atlantic salmon ( Salmo salar ) …”
Section: Resultsmentioning
confidence: 99%